Identification of House Dust Mite and the Risk Factor of Cronic Itch in Elderly - Novyan Lusiyana; Ekawati Suryaningsih, Betty; Kuspriyono, Onyxa; Widodo, Chaerul (Universitas Airlangga, 2024)
Introduction: Senile pruritus etiology is uncertain. However, well as intrinsic factors, one of the extrinsic risk factors causing pruritus is house dust mites (HDM) as. Aim of this study was to analyze the association between house dust mite density and the pruritus level among elderly residents. Methods: This is an observational study with cross-sectional design. The 34 elderly who met the criteria were included in this study. The pruritus level was obtained using questionnaire as to duration, degree, direction, disability, distribution (5D) itch scale based on NRS (numerical rating scale) categories divided into 4 categories (no, low, moderate, and severe itch). House dust mite density was checked using flotation method and the results categorized into low, moderate, and high density. The dust sample was checked for the species by microscope. The preventive activity to prevent the pruritus were also analyzed. The relationship between itch scale, preventive activity with HDM density was analyzed using STATA 17. Results and Discussion: A total of 34 elderly was included. Elderly were dominated with women (67.6%), moderate itch scale (38.2%) and moderate HDM density (58.8%). Most of the correlation between itch scale based NRS and preventive activity with HDM density p-value was not significant. But the elderly’s’ habit to clean the mattress was significantly correlated with HDM density (p=0.00). The Dermatophagoides sp were the dominant mites found in elderly’s’ room. Conclusion: Itch scale in elderly were not related with HDM density, but correlated with the habit to clean the mattress.